ANALISIS SISTEM EVALUASI KINERJA BERBASIS DIGITAL DAN WORK OVERLOAD DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT PLN UP3 LUBUK PAKAM (PENDEKATAN KUALITATIF) - Intania Amanda Putri; Putri Yunizar; Dewi Nur Aisah; Andhika Dharma Putri; Dwi Nur Akbar; Sari Wulandari (Journal Economic Management and Business, 2026)
This study aims to analyze the implementation of a digital-based performance evaluation system and work overload in improving employee performance at PT PLN (Persero) UP3 Lubuk Pakam. This research employs a qualitative method using observation and literature review as data collection techniques. The findings indicate that the implementation of a digital-based performance evaluation system has been effective in enhancing efficiency, transparency, and accuracy in assessing employee performance. The system also contributes to improved employee discipline, productivity, and overall work quality. However, some employees experience work overload due to high work targets and the large number of tasks that must be completed within a limited time frame. Work overload can positively affect productivity in the short term; however, if it occurs continuously, it may lead to fatigue, work stress, and a decline in performance quality. Therefore, maintaining a balance between the use of digital systems and proper workload management is essential to achieve optimal employee performance